2004
DOI: 10.1128/cmr.17.4.942-964.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microglia in Central Nervous System Infections

Abstract: The nature of microglia fascinated many prominent researchers in the 19th and early 20th centuries, and in a classic treatise in 1932, Pio del Rio-Hortega formulated a number of concepts regarding the function of these resident macrophages of the brain parenchyma that remain relevant to this day. However, a renaissance of interest in microglia occurred toward the end of the 20th century, fueled by the recognition of their role in neuropathogenesis of infectious agents, such as human immunodeficiency virus type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
507
1
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(531 citation statements)
references
References 372 publications
(354 reference statements)
12
507
1
11
Order By: Relevance
“…Following exposure to PRNP Sc , microglia produce neurotoxins that exacerbate neurodegeneration. 40,41 In contrast, it is reported elsewhere that activated microglia may afford protection to neurons through phagocytosis and digestion of aggregated PRNP Sc . 42,43 It is possible that the balance between the two contrary effects of microglial activation may proceed in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…Following exposure to PRNP Sc , microglia produce neurotoxins that exacerbate neurodegeneration. 40,41 In contrast, it is reported elsewhere that activated microglia may afford protection to neurons through phagocytosis and digestion of aggregated PRNP Sc . 42,43 It is possible that the balance between the two contrary effects of microglial activation may proceed in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, we analyzed the response of microglia to VSV infection in vivo. Microglia are believed to be the major resident cell type to mediate innate immune responses within the brain (5,10,12,21). We found that infected microglia produce type I IFN and that uninfected microglia are primed for a full type I IFN response in the context of brain infection.…”
mentioning
confidence: 70%
“…A similar study with LACV found nearly no type I IFN-expressing neurons but rather that glia expressed type I IFN (9). In addition, other innate immune pathways, such as the type II and III IFN responses (10,11), and inflammation (12), are activated by viral infection. These observations suggest a great deal of complexity in the brain's response to viral infection and raise several issues in need of clarification.…”
mentioning
confidence: 90%
“…We postulated that factors that caused an increase and activation of macrophages/microglia would lead to increased numbers of cerebellar heterokaryons. To test this hypothesis, we performed experiments using a well characterized compound, lipopolysaccharide (LPS), an endotoxin with a strong immunogenic response associated with leukocyte extravasation in vivo and activation of microglia leading to secretion of cytokines, chemokines, and prostaglandins 26 . Three 20-week-old BMT mice were chronically exposed to LPS before being sacrificed.…”
mentioning
confidence: 99%